PEMANFAATAN LIMBAH AIR CUCIAN BERAS SEBAGAI BAHAN BAKU PEMBUATAN BIOETANOL PADAT SECARA FERMENTASI OLEH Saccharomyces cerevisiae - Hervina Tri Oktavia (Jurnal Teknik Lingkungan, 2013)
Solid bioethanol is a solid fuel non-natural made by way of investment in bioethanol liquid fuel into the solid residue oil is stearic acid. Rice water as raw material for bioethanol manufacture solid because it has a carbohydrate content of 43% which can be hydrolyzed to glucose. Glucose can be converted into alcohol (ethanol) by fermentation. This study aims to determine the calorific value of solid bioethanol from waste rice water with a variety of tape yeast, time of fermentation, and variations of the addition of stearic acid. In this study, rice water hydrolyzed with strong acid HCl 7%. Furthermore tape fermented using yeast (Saccharomyces cerevisiae) with a variation of 25 grams, 35 grams and 45 grams for 3 days, 6 days, 9 days, and 12 days. The next stage is distilled in the temperature range 78 - 80oC. Results distillate with 77% plus levels of stearic acid with a variety of 100 grams, 150 grams and 200 grams. Calorific value resulting from the ethanol content of 77% with the addition of three variables stearic acid is 8760 kcal/kg, 9630 kcal/kg, and 10065 kcal/kg. The results of the solid old flame bioethanol best obtained on the addition of stearic acid is 200 grams for 6 minutes per 10 gram sample.